Penerapan Model Pembelajaran Complete Sentence dalam Meningkatkan Keterampilan Menulis Karangan - Wartini, Cucu (Mimbar Sekolah Dasar, 2017)
This research is motivated by the presence of serious problems in the aspect of essay writing skill. The purpose of this study is to know the improvment of student activity and student learning outcomes of writing essay skill material at 5th grade students of SDN Panyingkiran III Kabupaten Sumedang second semester in academic year 2015/2016, using complete sentenselearning.The research method used is classroom action research. Data collected through observation and tests. The result of this study for student activity, on first cycle 48% of students got very good criteria, second cycle 80% and third cycle 96%. For student learning outcomes, on first cycle just 40% students who pass the evaluation, second cycle 72% and third cycle 92%. Therefore, the process and learning outcomes got increased by using complete sentense on writing essay skill based experience.